PennyHow/PyTrx: PyTrx v1.2.4 - Penny How; Adrien Wehrlé (Zenodo, 2022)
PyTrx v1.2.4 is a sub-release to incorporate new changes and example scripts, coinciding with the submission of Messerli et al. (In Review) . Messerli et al. use PyTrx to delineate and georectify snow-covered areas on a small mountain glacier in Greenland. This PyTrx release continues on from the work that directly contributed to the publication of the PyTrx toolset in the following Frontiers in Earth Science paper: How et al. (2020) PyTrx: a Python-based monoscopic terrestrial photogrammetry toolset for glaciology. Frontiers in Earth Science, doi:10.3389/feart.2020.00021 Major changes since PyTrx v1.2.3 Inclusion of QAS example scripts and datasets Walkthrough guides on PyTrx's readthedocs pages PyTrx.CamEnv.calcDenseVelocity bug resolved with the addition of PyTrx.CamEnv.seedGridDEM and PyTrx.CamEnv.seedGridIM functionality DEM`